An audit of screening for anaemia and the characterising of red cell indices and ferritin in pregnancy in one hospital. (7th June 2011) - Yeh, P S; MacKillop, L; Harrington, D
Abstract : Introduction: As recommended by the National Collaborating Centre for Women's and Children's Health, our protocol screens for anaemia in pregnancy at booking and at 30 weeks. Iron supplementation is offered if Hb ≤11 g/100 ml or mean cell volume (MCV) <82 fl. If Hb ≥11 g/100 ml, ferritin is measured and iron supplementation is offered if ferritin ≤ 30 mcg/l. Aims: The aims were to establish adherence to national guideline and the characteristics of the red cell indices and ferritin as gestation advances. Methods: The first 50 consecutive women delivered from the January 1 2009 were selected. Information was obtained from hospital notes and laboratory records. Results: From the 50 women, 168 FBC samples were taken. The mean Hb, MCV and haematocrit (HCT) were 11.9 g/100 ml±0.9 (range 9.2–13.8); 88.0 fl±4.6 (range 72.1–97.2); and 0.35±0.03 (range 0.28–0.40) respectively. Both booking and 30 week FBC were done in 40 (92%) cases; 3 (6%) at 30 week (due to transfer of care from other units) and 1 (2%) at booking. 27 (54%) of the 50 women had MCV<82 or Hb ≤11 at any time. 18 (67%) has documentation of prescribed iron. Where Hb>11.0, ferritin was measured in 16 (32%) of cases and 82% had ferritin ≤30 mcg/dl. Conclusion: Adherence to guideline is good (98%) for blood sampling but less good (67%) in the prescription of iron. Where Hb ≥11 g/100 ml, majority (82%) had ferritin ≤30 mcg/dl. Hb and HCT tend to fall in second trimester and rises again in the third trimester. MCV tends to rise slightly and steadily throughout gestation.